Real-World Effectiveness of Single-Inhaler Triple Treatment Through Assorted Respiratory Outcomes When Switched From Multiple-Inhaler Triple Therapies (RESTART): A Prospective Cohort Study of Korean Patients With COPD - Lim H; Kim DH; Hong SH; Shin J; Lee H; Shin K; Ra SW; Lee SJ (International Journal of COPD)
Hana Lim,1,* Dong Han Kim,2,* Song Hee Hong,2 Juyoung Shin,1 Hyesung Lee,3 Kyeongcheol Shin,4 Seung Won Ra,5,6 Seung Jun Lee7,8 1Department of Bio Health Regulatory Science, Sungkyunkwan University, Suwon, Korea; 2Department of Social Pharmacy, Seoul National University, Seoul, Korea; 3Department of Medical Informatics, Kangwon National University College of Medicine, Chuncheon, Korea; 4Division of Pulmonology and Allergy, Regional Center for Respiratory Disease, Yeungnam University Medical Center, Yeungnam University College of Medicine, Daegu, Korea; 5Division of Pulmonology, Department of Internal Medicine, Ulsan University Hospital, University of Ulsan College of Medicine, Ulsan, Korea; 6Basic-Clinical Convergence Research Institute, University of Ulsan, Ulsan, Korea; 7Division of Pulmonology, Department of Internal Medicine, Gyeongsang National University, Jinju, Korea; 8Division of Pulmonology, Department of Internal Medicine, Good & Strong Clinic, Jinju, Korea*These authors contributed equally to this workCorrespondence: Seung Won Ra, Division of Pulmonology, Department of Internal Medicine, Ulsan University Hospital, University of Ulsan College of Medicine, Ulsan, Korea, Email docra@docra.pe.kr Seung Jun Lee, Department of Internal Medicine, Good & Strong Clinic, Jinju, Korea, Email juny2278@naver.comPurpose: Chronic obstructive pulmonary disease (COPD) is a progressive respiratory condition characterized by persistent airflow limitation, leading to significant morbidity and mortality. Despite the effectiveness of multiple inhaler triple therapy (MITT), its complexity often results in poor adherence and suboptimal outcomes. Transitioning to single inhaler triple therapy (SITT) may enhance adherence, leading to improved clinical outcomes and quality of life of patients. The Real-World Effectiveness of Single Inhaler Triple Treatment through Assorted Respiratory Outcomes when Switched from Multiple Inhaler Triple Therapies (RESTART) study aimed to evaluate the clinical benefits of switching from MITT to SITT using fluticasone furoate/umeclidinium/vilanterol (FF/UMEC/VI) in a real-world Korean setting.Patients and Methods: This prospective, multicenter, observational study enrolled 107 patients, aged 40 and older, with diagnosed COPD, all previously on MITT. The patients were transitioned to once-daily FF/UMEC/VI administered via the ELLIPTA inhaler. The primary outcome was a change in the COPD Assessment Test (CAT) score after 24 weeks. The secondary outcomes included changes in lung function, exacerbation rates, Modified Medical Research Council Dyspnea Scale scores, and Treatment Satisfaction–Visual Analysis Scale (TS-VAS) scores.Results: A total of 91 patients completed the 24-week observation. CAT scores significantly improved (mean change = 1.40 points, P = 0.007). Lung function also improved, with a mean increase in the FEV1/FVC ratio (mean change = 4.31%, P = 0.005). Exacerbation rates decreased significantly (incidence rate ratio = 0.45, P = 0.016). Treatment satisfaction increased, with a mean TS-VAS score rise of 1.71 points (P < 0.001).Conclusion: The transition from MITT to SITT significantly improved COPD symptom management, pulmonary function, exacerbation rate, and treatment satisfaction in Korean cohort. Using a single inhaler to simplify therapy might increase patient compliance and improve clinical outcomes of COPD management.Keywords: real-world evidence, single-inhaler triple treatment, chronic obstructive pulmonary disease, adherence, chronic obstructive pulmonary disease assessment test score